2014
DOI: 10.4238/2014.january.17.4
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive outcomes in recurrent pregnancy loss associated with a parental carrier of chromosome abnormalities or polymorphisms

Abstract: ABSTRACT. The subsequent reproductive outcomes in couples with a history of recurrent pregnancy loss (RPL) associated with chromosome abnormalities or polymorphisms are generally not reported in China. Many RPL carrier couples have decided not to have children. The present study recorded the subsequent delivery, miscarriage, and unpregnancy outcomes of 113 RPL carrier couples and 226 non-carrier couples, and compared differences in reproductive outcomes between couples with different types of chromosome abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…Similarly, previous reports have indicated a correlation between the breakpoints at 4q13, 4q21, 4q25, 4q32, and 4q35 with recurrent abortions and reproductive failures [10,11]. A study in 69 patients by [16].…”
Section: Resultssupporting
confidence: 56%
“…Similarly, previous reports have indicated a correlation between the breakpoints at 4q13, 4q21, 4q25, 4q32, and 4q35 with recurrent abortions and reproductive failures [10,11]. A study in 69 patients by [16].…”
Section: Resultssupporting
confidence: 56%
“…The chance for their offspring to have an unbalanced translocation can be minimized [6,11,12]. When chromosomal abnormality carriers and non-carriers were compared, no significant difference was observed between them in the number of live births [7]. This study confirms that apart from chromosomal defects, there are other aetiologies to RPL.…”
Section: Structural Chromosomal Abnormalitiessupporting
confidence: 64%
“…Numerical chromosomal abnormalities in parents, resulting in abortion are not as common as structural abnormalities but of them, aneuploidies involving the X chromosome are the most commonly observed [6]. In a study conducted in China, only 0.18% of the 137 RPL carriers had chromosomal abnormalities whereas balanced translocations dominated [7]. A comparative study was done between spontaneous abortion (SA) and RPL using the aborted foetuses and it was found that the number of chromosomal abnormalities were significantly higher in RPL than in SA.…”
Section: Aneuploidymentioning
confidence: 99%
“…Guo et al (2012) reported that chromosomal polymorphisms seem to have deleterious effects on spermatogenesis, contributing to male infertility. Dong et al (2014) reported that chromosomal polymorphisms do not have significantly lower live birth rates than non-carrier couples. For male translocation carriers, the success rates of natural pregnancies and live birth rates range from 30 to 70% (Ozawa et al, 2008;Kochhar and Ghosh, 2013;Flynn et al, 2014).…”
Section: Discussionmentioning
confidence: 99%